On Nörlund I2-lacunary statistical convergence of double sequences in intuitionistic fuzzy normed spaces - Kişi, Ömer; Gürdal, Mehmet; Choudhury, Chiranjib; Kişi, Ömer; Kişi, Ömer (Comenius University in Bratislava, 2024)
Investigating the concepts of Nörlund I2-lacunary statistical convergence and extremely intuitionistic Nörlund I2-lacunary convergence of double sequence in intuitionistic fuzzy normed spaces (IFNS) is the goal of this article. Then, we introduce the concepts of Nörlund strongly I2 *}-lacunary convergence, Nörlund strongly I2-lacunary Cauchy, and Nörlund strongly I2 *}-lacunary Cauchy double sequences in IFNS and get astounding results. © 2024 Elsevier B.V., All rights reserved.
Keywords: Ideal Convergence; Intuitionistic Normed Spaces; Nörlund Convergent Space